A natureza multimodal de uma constelação de gêneros cartas - Lopes, Ana Keyla Carmo (www.teses.ufc.br, 2014)
LOPES, Ana Keyla Carmo. A natureza multimodal de uma constelação de gêneros cartas. 2013. 262f. – Tese (Doutorado) – Universidade Federal do Ceará, Departamento de Letras Vernáculas, Programa de Pós-graduação em Linguística, Fortaleza (CE), 2013. === Submitted by Márcia Araújo (marcia_m_bezerra@yahoo.com.br) on 2014-06-06T14:56:41Z No. of bitstreams: 1 2013-tese-akclopes.pdf: 6362024 bytes, checksum: af2523d87d5cfeee3a5419ef5900e566 (MD5) === Approved for entry into archive by Márcia Araújo(marcia_m_bezerra@yahoo.com.br) on 2014-06-06T17:26:16Z (GMT) No. of bitstreams: 1 2013-tese-akclopes.pdf: 6362024 bytes, checksum: af2523d87d5cfeee3a5419ef5900e566 (MD5) === Made available in DSpace on 2014-06-06T17:26:16Z (GMT). No. of bitstreams: 1 2013-tese-akclopes.pdf: 6362024 bytes, checksum: af2523d87d5cfeee3a5419ef5900e566 (MD5) Previous issue date: 2013 === In this paper, we analyze how multimodality (specifically, through the principles of visual composition within the nonverbal or visual language, and through the field [field], relations [tenor], mode [mode] and schematic structure within the verbal written language) cuts across the constellation of genre letters as well as how the principles of visual composition interact with social (field) or communicative purposes of each genre letter that will be analyzed in this research. For this, we follow the theoretical proposal of Kress; van Leeuwen (2006), which point out to three principles of visual composition of genres, which are interrelated, the informative value (given and new, real and ideal as well as center and margin), the salience and framing (the frame) and the design of constellation, according to Araújo (2006), the notions of communicative purposes of Askehave; Swales (2001, 2009) and Swales (2004), the concepts of field (field) or social purpose, relations (tenor), mode (mode), Martin; Rose (2008), and the design of schematic structure by Martin (1992). A sample of 70 copies of genre letters has been analyzed as follows: a) 10 cover letters or letters of application (employment), b) 10 chain letters, c) 10 literary letters (5 letters directed to children and teenagers, 5 letters to adult audiences) d) 10 letters to the reader, e) 10 letters from the reader, f) 10 religious letters, g) 10 letters of appreciation. After the analysis, in which we use the program WordSmith Tools, we verify that, in relation to written verbal language, in the mode, the most recurrent and meaningful lexical items in each genre. Moreover, the approach of the relations concerning social actors of the field, appointed by social or communicative purposes and the schematic structure of the letters seem very relevant and productive, as it reveals the peculiar characteristics of these genres, in the context of language. Regarding visual language, the principle of projection proved productive and recurrent in all genres once that the writers of these letters mainly look forward to catching the attention of “consumers” by highlighting some information, intending thereby an interaction of “consumers” with these cards and a position about them, which, for example, can relate to the acceptance of the communicative intent of this producer. The framing (frame) is present in almost all genres except in literary letters (aimed at adults). The informative value (given and new, ideal and real, center and margin) does not provide an actual occurrence despite the fact that the couple has been identified in corpus, possibly due to the fact that these pairs may “stifle” the dynamic character of the existing visual language in the genres studied. In short, the study of verbal and visual language writing these genres is of importance for a better understanding of the characteristics peculiar to each. === Neste trabalho, analisamos como a multimodalidade (especificamente, através dos princípios de composição visual, no âmbito da linguagem não-verbal ou visual, e através do campo [field], das relações [tenor], do modo [mode] e da estrutura esquemática, no âmbito da linguagem verbal escrita) perpassa a constelação de gêneros cartas. Verificamos, também, como os princípios da composição visual interagem com os propósitos sociais (campo) ou comunicativos de cada uma das amostras dos gêneros cartas. Para isso, seguimos a proposta teórica de Kress; van Leeuwen (2006), que apontam três princípios da composição visual de gêneros, os quais são inter-relacionados, o valor informativo (dado e novo, ideal e real, centro e margem), a saliência e o framing (a moldura); assim como a concepção de constelação, de Araújo (2006); as noções de propósitos comunicativos, de Askehave; Swales (2001; 2009) e Swales (2004); as concepções de campo (field) ou propósito social, relações (tenor), modo (mode), de Martin; Rose (2008); e a concepção de estrutura esquemática, de Martin (1992). Analisamos uma amostra composta por 70 exemplares de gêneros cartas, assim distribuídos: a) 10 cartas de apresentação; b) 10 cartascorrentes; c) 10 cartas literárias (5 cartas direcionadas ao público infanto-juvenil; 5 cartas, ao público adulto); d) 10 cartas ao leitor; e) 10 cartas do leitor; f) 10 cartas religiosas; g) 10 cartas de agradecimento. Após a análise, na qual usamos o programa WordSmith Tools, verificamos, em relação à linguagem verbal escrita, no modo, os itens lexicais mais recorrentes e mais significativos em cada gênero. Além disso, observamos que a abordagem das relações (atores sociais), do campo (propósitos sociais ou comunicativos) e da estrutura esquemática dessas cartas se mostra relevante, pois revela as características inerentes a esses gêneros, nesse âmbito da linguagem. No que diz respeito à linguagem visual, a saliência mostra-se produtiva e recorrente em todas as amostras, uma vez que os produtores das cartas em questão procuram, principalmente, atrair a atenção dos “consumidores”, através do destaque de algumas informações, pretendendo, com isso, uma interação dos “consumidores” com essas cartas e um posicionamento a respeito delas, o qual, por exemplo, pode se relacionar com a aceitação da intenção comunicativa desse produtor. O framing (moldura) está presente em quase todos os gêneros, exceto nas cartas literárias (direcionadas ao público adulto). O valor informativo (dado e novo, ideal e real, centro e margem) não apresenta uma ocorrência efetiva apesar de os pares serem identificados no corpus, possivelmente, devido ao fato de que esses pares podem “engessar” o caráter dinâmico da linguagem visual existentes nos gêneros em estudo. Em suma, o estudo da linguagem verbal escrita e da linguagem visual desses gêneros revela-se importante para o melhor entendimento das características peculiares a cada um deles.